Assessment of a fast method to predict the biochemical methane potential based on biodegradable COD obtained by fractionation respirometric tests. (1st September 2020) - Argiz, L.; Reyes, C.; Belmonte, M.; Franchi, O.; Campo, R.; Fra-Vázquez, A.; Val del Río, A.; Mosquera-Corral, A.; Campos, J.L.
Abstract: The biochemical methane potential test (BMP) is the most common analytical technique to predict the performance of anaerobic digesters. However, this assay is time-consuming (from 20 to over than 100 days) and consequently impractical when it is necessary to obtain a quick result. Several methods are available for faster BMP prediction but, unfortunately, there is still a lack of a clear alternative. Current aerobic tests underestimate the BMP of substrates since they only detect the easily biodegradable COD. In this context, the potential of COD fractionation respirometric assays, which allow the determination of the particulate slowly biodegradable fraction, was evaluated here as an alternative to early predict the BMP of substrates. Seven different origin waste streams were tested and the anaerobically biodegraded organic matter (CODmet ) was compared with the different COD fractions. When considering adapted microorganisms, the appropriate operational conditions and the required biodegradation time, the differences between the CODmet, determined through BMP tests, and the biodegradable COD (CODb ) obtained by respirometry, were not significant (CODmet (57.8026 ± 21.2875) and CODb (55.6491 ± 21.3417), t (5) = 0.189, p = 0.853). Therefore, results suggest that the BMP of a substrate might be early predicted from its CODb in only few hours. This methodology was validated by the performance of an inter-laboratory studyconsidering four additional substrates. Graphical abstract: Image 1 Highlights: A novel and rapid methodology for BMP prediction based on COD fractionation. Eleven substrates of diverse nature, origin and complexity were tested. Methanized COD coincided with biodegradable soluble + particulate fractions. Testing time was reduced from weeks-months (BMP) to hours-days (COD fractionation). An interlaboratory comparison validated the developed methodology.